Miconia lorenaensis (Melastomataceae), a new species from Colombian Andes - Murillo-Serna, Jhon S.; Londoño-Echeverri, Yeison; David-Higuita, Heriberto (Phytotaxa, 2021)
A new species of Melastomataceae from the Andes of Colombia is described and illustrated. Miconia lorenaensis is part of Miconia sect. Amblyarrhena, and it differs from other species in this group by the combination of branches, petioles and leaves covered by scattered short dendritic trichomes, 7-nerved peltate leaves, acuminate or cuspidate apex with a circinate-thickened tip and flowers with completely inferior, 3-locular ovary. Comments about its distribution, habitat, phenology and taxonomic affinities are provided.